2001
DOI: 10.1074/jbc.c000824200
|View full text |Cite
|
Sign up to set email alerts
|

Deacetylase Activity Associates with Topoisomerase II and Is Necessary for Etoposide-induced Apoptosis

Abstract: DNA topoisomerase II (topo II) is a ubiquitous nuclear enzyme that is involved in DNA replication, transcription, chromosome segregation, and apoptosis.Here we show by immunoprecipitation, pull down with glutathione S-transferase fusion proteins, and yeast two-hybrid analysis that both topo II␣ and -␤ physically interact with the histone deacetylase HDAC1. The in vitro DNA decatenation activity of recombinant topo II␣ and -␤ is inhibited by association with catalytically inactive, recombinant HDAC1. We provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
65
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 28 publications
0
65
0
Order By: Relevance
“…One such protein is Topo II␣, which is a major component of the chromosomal scaffold/matrix (43) that has been shown to be enriched at the 10q25 neocentromere (5). A direct interaction between Topo II␣ and the histone deacetylases HDAC-1 and HDAC-2 has been described in mammalian cells, with protein complexes containing these proteins demonstrating both deacetylation and topoisomerase activities (44,45). Furthermore, TSA has been shown to disrupt the association of other scaffold/matrix proteins (46 -48).…”
Section: Discussionmentioning
confidence: 99%
“…One such protein is Topo II␣, which is a major component of the chromosomal scaffold/matrix (43) that has been shown to be enriched at the 10q25 neocentromere (5). A direct interaction between Topo II␣ and the histone deacetylases HDAC-1 and HDAC-2 has been described in mammalian cells, with protein complexes containing these proteins demonstrating both deacetylation and topoisomerase activities (44,45). Furthermore, TSA has been shown to disrupt the association of other scaffold/matrix proteins (46 -48).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the POK protein FAZF has been recently shown to interact with the Fanconi Anemia gene FANCC and to form nuclear dots at or nearby RF, suggesting that POK proteins may be implied in replication and DNA damage repair (Dai et al, 2002). We thus have subjected the induced UTA-L cells to DNA injuries, either upon treatment with topoisomerases poisons (etoposide or camptothecine; Johnson et al, 2001;Suzuki et al, 2001) or to UV irradiation (either UVA or UVC). However, we never found that these treatments are able to mimic or potentiate the effects of BrdU on RF localization with respect to BCL6 bodies (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…We incubated the cell suspension on ice for 30 min with gentle stirring, sonicated it on ice and clarified it by centrifuging at 13,000g for 5 min. We processed the supernatant for immunoprecipitation using 5 µg of purified mouse monoclonal antibody to hemagglutinin or antibody to syntaxin7 coupled to protein G-or protein A-sepharose beads (Amersham Biosciences) 30 . …”
Section: Immunoprecipitation Of Immunocomplexesmentioning
confidence: 99%